Development of E-Modul Assisted with Software Unity on Trade Receivables Materials for Class XI AKL at SMKN 1 Jember - Damayanti, Devi; Sedyati, Retna Ngesti; Herlindawati, Dwi (Future Science, 2024)
Digital technology is experiencing very rapid development in all aspects of life, including the educational aspect. This means that teachers must be able to keep up with technological advances. One thing teachers can do is develop and adapt learning materials, for example by developing teaching materials that are integrated with digital technology. However, in reality teachers often experience obstacles in developing teaching materials. One of them, like the phenomenon at SMKN 1 Jember, is that teachers have limi-tations in developing technology-integrated teaching materials. XI AKL 1 students still use text-based textbooks which are still too monotonous and the textbook material is no longer relevant to the learning objectives. So other alternative teaching materials are needed to support learning. The aim of this research is to produce a product in the form of a financial ac-counting e-module assisted by Unity software on accounts receivable ma-terial that is appropriate in terms of content/material, presentation and graphics for class XI AKL at SMKN 1 Jember. This development research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research trial subjects consisted of expert validators and the trial targets, namely class XI AKL 1 students. The data collection technique used a questionnaire which was then analyzed using a Likert scale. The results of the analysis from validating the feasibil-ity of the e-module showed that the feasibility of the content/material was 96. 6 % and the validation of the feasibility of presentation and graphics was 86%. Then the analysis results from the student response test ob-tained a score of 95%. From these results, the e-module is very suitable for use as an alternative teaching material in financial accounting learning ac-tivities. The conclusion from this development research is that the e-module product developed is very suitable for use in learning, the e-module makes it easier for students to understand the material, increases stu-dents' enthusiasm in reading learning material, and raises students' enthu-siasm for learning.